Is Foreign Exchange Risk Priced in the Japanese Stock Market? - Choi, Jongmoo Jay; Hiraki, Takato; Takezawa, Nobuya (Journal of Financial and Quantitative Analysis, 1998)
Jongmoo Jay Choi, Takato Hiraki, Nobuya Takezawa, Is Foreign Exchange Risk Priced in the Japanese Stock Market?, The Journal of Financial and Quantitative Analysis, Vol. 33, No. 3 (Sep., 1998), pp. 361-382